The Uncertain Subject of Depression, or End-of-the-Century Individuality - Ehrenberg, Alain (Weariness of the Self, 2009)
The ability to act by oneself is at the heart of socialization, and the breakdown of action is the fundamental disorder of depression. There are two ways of understanding the situation: one is concerned only with the subject of conflict, the other has nothing to do with conflict. The controversy between Janet and Freud was played out a century later in a completely different normative and psychiatric context. If depression really is the double pathological manifestation of psychic liberation and individual initiative, then, necessarily, internal splits other than those of conflict will be played out. At the psychiatric level, today